Academic Stress and Drug Abuse as Factors Inhibiting Psychological Well-Being Among Undergraduates: It’s Counselling Implications - Bukoye, Roseline Olufunke (European Scientific Journal, ESJ, 2017)
The study examined Academic Stress and drug abuse as factors inhibiting psychological well-being among undergraduate students and its counselling implications. Three faculties in IBB University were purposively selected for the study and 90 students were randomly selected in the three faculties for the study. Three instruments (PPPWQ, ASRS. and DAST.) that were validated by experts and with confirmed reliabilities were used for the study. Each instrument was administered on the respondents and retrieved by the researcher with the efforts of 3 research assistants.Simple percentage, Rank order and chi-square were used for bio-data and the analysis of data respectively. The findings revealed that, lack of time management, text anxiety, uncoverage of course contents and difficult in course component are the causes of academic stress among students. The intake of drugs makes the students feel lonely, sexual urge, Bullying, poor Odour, among others, Sweating, accelerated heart rate, trembling, maladjustment, fear of failure, among others are the nasty effects of academic stress and drug abuse on their personalities as such, inhibiting their psychological well-being. It was vividly seen that academic stress and drug abuse are significant factors that inhibit psychological well-being of students. Based on the findings, the counsellor could use systematic desensitization technique to discourage drug use among students and seminars, advocacy programmes, among others, are recommended to help the students.